Plasma mEV levels in Ghanain malaria patients with low parasitaemia are higher than those of healthy controls, raising the potential for parasite markers in mEVs as diagnostic targets. Issue 1 (1st January 2020) - Antwi-Baffour, Samuel; Malibha-Pinchbeck, Memory; Stratton, Dan; Jorfi, Samireh; Lange, Sigrun; Inal, Jameel
ABSTRACT: This study sought to measure medium-sized extracellular vesicles (mEVs) in plasma, when patients have low Plasmodium falciparum early in infection. We aimed to define the relationship between plasma mEVs and: (i) parasitaemia, (ii) period from onset of malaria symptoms until seeking medical care (patient delay, PD), (iii) age and (iv) gender. In this cross-sectional study, n = 434 patients were analysed and Nanosight Tracking Analysis (NTA) used to quantify mEVs (vesicles of 150–500 nm diameter, isolated at 15, 000 × g, β-tubulin-positive and staining for annexin V, but weak or negative for CD81). Overall plasma mEV levels (1.69 × 10 10 mEVs mL −1 ) were 2.3-fold higher than for uninfected controls (0.51 × 10 10 mEVs mL −1 ). Divided into four age groups, we found a bimodal distribution with 2.5- and 2.1-fold higher mEVs in infected children (<11 years old [yo]) (median:2.11 × 10 10 mEVs mL −1 ) and the elderly (>45 yo) (median:1.92 × 10 10 mEVs mL −1 ), respectively, compared to uninfected controls; parasite density varied similarly with age groups. There was a positive association between mEVs and parasite density (r = 0.587, p < 0.0001) and mEVs were strongly associated with PD (r = 0.919, p < 0.0001), but gender had no effect on plasma mEV levels ( p = 0.667). Parasite density was also exponentially related to patient delay. Gender ( p = 0.667) had no effect on plasma mEV levels. During periods of low parasitaemia (PD = 72h), mEVs were 0.93-fold greater than in uninfected controls. As 75% (49/65) of patients had low parasitaemia levels (20–500 parasites µL −1 ), close to the detection limits of microscopy of Giemsa-stained thick blood films (5–150 parasites µL −1 ), mEV quantification by NTA could potentially have early diagnostic value, and raises the potential of Pf markers in mEVs as early diagnostic targets.